INVESTIGATION OF MECHANICAL PROPERTIES OF COW BONE AND POULTRY FEATHER REINFORCED rLDPE COMPOSITES FOR SUSTAINABLE MATERIAL APPLICATIONS - Adah, Patrick Ushie; Ubi, Ateb Paschal; Salawu, Asipita Abdulrahman; Salami, Wasiu Oyeyemi (FUDMA Journal of Sciences, 2024)
Materials with an unusual mix of properties which cannot be satisfied by traditional polymeric materials are increasingly researched alongside the conversion of waste to wealth, promoting the sustainability of engineering materials. This study investigated the mechanical properties of cow bone (CB) and pyrolyzed poultry feather (PF) reinforced recycled low-density polyethene (rLDPE) composites to assess their suitability as substitutes for conventional polymers in industrial applications. CB was crushed and blended at different ratios with PF in an rLDPE matrix obtained from waste sachet water packs. The composites were developed and tested for hardness, tensile, flexural and impact strength as well as moisture absorption. Results obtained from the mechanical tests showed that the composite with 70% rLDPE and 30% PF resulted in the highest tensile strength and Shore-D hardness of 6.42 MPa and 94 respectively. The composite having 70% rLDPE and 30% CB resulted in the highest flexural strength of 10.81 MPa while the composite with 80% rLDPE and 20% CB absorbed the highest impact energy of 3.07 J. All samples except the composite having 70% rLDPE, 20% CB and 10% PF absorbed less than 5% moisture. The developed composites showed good lightweight characteristics with density values ranging from 0.74 g/cm3 to 1.07 g/cm3. Compared to traditional polymers, these composites offer improved sustainability and moderate mechanical properties but may have lower durability unless treated for moisture resistance. They can serve as cheap substitutes for synthetic polymers used in the manufacture of casings and packaging materials in the electronics, beverage and automobile industries.